THE EFFECT OF SALES GROWTH, COMPANY SIZE AND CAPITAL INTENSITY ON TAX AVOIDANCE WITH AUDIT COMMITTEE AS A MODERATING VARIABLE IN MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2020-2023 - Juni Vivi Engjelina Sianturi; Fahmi Natigor Nasution; Yeni Absah (CV. Radja Publika, 2025)
This study aims to examine the effect of sales growth, company size, and capital intensity on tax avoidance with the audit committee as a moderating variable. This study utilized 66 mining companies listed on the Indonesia Stock Exchange (IDX). With Purposive Sampling Technique with a total sample of 88 companies during the period 2020 to 2023. The research data is in the form of secondary data obtained from previously published annual reports by accessing the official site of the Indonesia Stock Exchange website at www.idx.co.id. Data analysis was carried out using Moderated Regression Analysis (MRA) with SPSS 30 software. The results of the study showed that sales growth, company size and capital intensity had a positive and significant effect on tax avoidance. However, when sales growth, company size and capital intensity were moderated by the audit committee, their influence was negative (weakening) and significant on tax avoidance.